Strategy, concept and productivity of goat milk and cheese: A bibliographical review (Research, Society and Development, 2023)
Goat milk has great socioeconomic importance in food production in the Brazilian Northeast, with goat farming being one of the main activities carried out in the Semi-Arid region. It is important to highlight that the Semiarid Paraibano is characterized by environmental conditions of arid lands and low rainfall, where goats have their main food source in the Caatinga biome, which, added to the recognized nutritional value of goat milk, makes it play a role in complementary feeding for children in this region. As goat milk is a highly digestible food with high nutritional value, consumption of this product has been increasing due to the demand for dairy products (with an emphasis on cheese) and problems with allergies to bovine milk. Therefore, the study aims to conceptualize goat milk and cheese in terms of innovation, trends, productivity and impact on health through an narrative bibliographic review. The methodological approach allowed the use of experimental and non-experimental studies to have a complete understanding of the proposed theme. Goat milk has a composition rich in proteins, vitamins, especially vitamin A, fat, dry extract, carbohydrates and mineral salts, which are essential for humans. Therefore, it is of interest to further study the functional potential of the compounds present in goat cheese, enabling alternative processing of the raw material, goat milk.